Constant voltage stress characterization of nFinFET transistor during total ionizing dose experiment. (September 2018) - Li, B.; Huang, Y.; Wu, J.; Huang, Y.; Li, B.; Zhang, Q.; Yang, L.; Wan, F.; Luo, J.; Han, Z.; Yin, H.
Abstract: During the lifetime of integrated circuits in the space environment, they encounter radiation degradation, such as the total ionizing dose (TID) effect as well as intrinsic degradation mechanisms, such as the constant voltage stress (CVS) effect. This paper analyzes the effects of TID and CVS on the nFinFET with a high-κ (HfO2 ) metal gate (HKMG). Various dimensions and stress voltages on nFinFETs are characterized under room temperature. Experimental results show that both effects can cause the threshold voltage (Vth ) of the transistor to shift towards positive. Compared with TID-induced degradation, the devices appear relatively robust against CVS. Highlights: Total ionizing dose responses and Bias temperature instability of N type FinFETs are investigated. Geometry and bias condition dependences of BTI were studied in room temperature. Difference of threshold voltage is the main reason for longer gate length transistor has a larger degradation.